Enhanced accumulation of phenolics in pea (Pisum sativum L.) seeds upon foliar application of selenate or zinc oxide - Malka, Maksymilian; Du Laing, Gijs; Kurešová, Gabriela; Hegedüsová, Alžbeta; Bohn, Torsten (Frontiers in Nutrition, 2023)
Background Selenium (Se) and zinc (Zn) are essential antioxidant enzyme cofactors. Foliar Se/Zn application is a highly effective method of plant biofortification. However, little is known about the effect of such applications on the concentration of trace elements and phytochemicals with pro-oxidant or antioxidant activity in pea (Pisum sativum L.). Methods A 2-year pot experiment (2014/2015) was conducted to examine the response of two pea varieties (Ambassador and Premium) to foliar-administered sodium selenate (0/50/100 g Se/ha) and zinc oxide (0/375/750 g Zn/ha) at the flowering stage. Concentrations of selected trace elements (Fe, Cu, and Mn), total phenolic content (TPC), total flavonoid content (TFC), and total antioxidant activity (ABTS, FRAP) of seeds were determined. Results and conclusions Se/Zn treatments did not improve the concentration of trace elements, while they generally enhanced TPC. Among examined treatments, the highest TPC was found in Ambassador (from 2014) treated with 100 g Se/ha and 750 g Zn/ha (2,926 and 3,221 mg/100 g DW, respectively) vs. the control (1,737 mg/100 g DW). In addition, 50 g of Se/ha increased TFC vs. the control (261 vs. 151 mg/100 g DW) in Premium (from 2014), 750 g of Zn/ha increased ABTS vs. the control (25.2 vs. 59.5 mg/100 g DW) in Ambassador (from 2015), and 50 g of Se/ha increased FRAP vs. the control (26.6 vs. 18.0 mmol/100 g DW) in Ambassador (from 2015). In linear multivariable regression models, Zn, Mn, Cu, and TPC best explained ABTS (R = 0.577), while Se, Cu, and TPC best explained the FRAP findings (R = 0.696). This study highlights the potential of foliar biofortification with trace elements for producing pea/pea products rich in bioactive plant metabolites beneficial for human health.